2014
DOI: 10.1002/uog.13206
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with preterm delivery after fetoscopic laser ablation for twin-twin transfusion syndrome

Abstract: OBJECTIVE Despite improved perinatal survival following fetoscopic laser surgery (FLS) for twin twin transfusion syndrome (TTTS), prematurity remains an important contributor to perinatal mortality and morbidity. The objective of the study was to identify risk factors for complicated preterm delivery after FLS. STUDY DESIGN Retrospective cohort study of prospectively collected data on maternal/fetal demographics and pre-operative, operative and post-operative variables of 459 patients treated in 3 U.S. fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…In TTTS, iPPROM rates up to 50% have been reported, although the exact incidence of surgery-related rupture versus the increased baseline risk of PPROM in monochorionic twins is difficult to determine. Several recent series from large fetal centers have reported a 28-42% incidence of iPPROM before 32 weeks of gestation of [6,12]. Notably, the risk of rupture of membranes is twice as high in twin gestations as in singleton gestations [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In TTTS, iPPROM rates up to 50% have been reported, although the exact incidence of surgery-related rupture versus the increased baseline risk of PPROM in monochorionic twins is difficult to determine. Several recent series from large fetal centers have reported a 28-42% incidence of iPPROM before 32 weeks of gestation of [6,12]. Notably, the risk of rupture of membranes is twice as high in twin gestations as in singleton gestations [13].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, reported rates of iPPROM range from 2 to 50% [5], with a recent systematic review reporting an average rate of 27% [4]. Most recently, a multicenter retrospective study examining the risk factors associated with preterm delivery after fetoscopic laser ablation reported an overall iPPROM rate prior to 32 weeks of gestation of 28% [6], while the multicenter prospective randomized control study on the Solomon technique reported iPPROM rates before 32 weeks of 34-42% [7]. Several risk factors for iPPROM have been identified, including the size and number of ports used, duration of the procedure, type of anesthesia, gestational age (GA) at intervention, placental location, and operator experience [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that mechanical injury to the fetal membranes triggers a cascade of events yet to be determined that ultimately induces generalized cell death of the recipient's amniochorion; Alternatively or concurrent changes in the AF milieu due to the pathophysiology of the TTTS or related to amnioinfusion of LR solution during surgery may affect the concentration of essential nutrients required to sustain viability of the fetal membranes and in particular amnion (10,21). The latter possibility is supported by our observation that the recipient's AF had significantly lower levels of glucose, proteins, and LDH levels, suggestive of polyhydramnios-induced dilution.…”
Section: Articlesmentioning
confidence: 99%
“…Aside from the cost of caring for the premature infants, preterm delivery is directly associated with long-term neurological deficits in TTTS (4,6), undermining the complete benefits of such intervention. PPROM which affects 20-32% of cases is the most important risk factor leading to preterm delivery (2,(7)(8)(9)(10).…”
mentioning
confidence: 99%